The Influence of the Student Team Achievement Division (STAD) Learning Model on the Learning Motivation of Class VII Students in Arabic Subjects at SMPI Rabbanii Islamic School Cikarang - Chaniar Tanara; Iwan Hermawan; Nur Aini Farida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research is based on the problem of learning activities experienced by students, namely low motivation to learn Arabic. During the learning process, it can be seen that some students do not focus on paying attention, students are engrossed in chatting with their classmates, and are sleepy during lessons. The purpose of this study is to find out whether the STAD learning model has an effect on the learning motivation of grade VII students at SMPI Rabbanii Islamic School Cikarang. The type of research used in this study is quantitative with a correlation method. In this study, sampling used a saturated sample, namely the entire population as a sample in the study. The data collection technique uses a questionnaire instrument aimed at all grade VII students at SMPI Rabbanii Islamic School Karawang. The data analysis technique uses descriptive analysis and inferential analysis. Based on the analysis, the results of the simple linear regression test of 0.000<0.05 can be concluded that the STAD learning model variable (X) has an effect on the learning motivation variable of students (Y). To find out the amount of influence of the learning model X on Y can be seen from the summary model, it is obtained (R Square) of 0.502, meaning that the percentage of influence of the learning model variable STAD (X) affects the learning motivation variable of students (Y), which is 50.2%, the rest is influenced by other factors.